2004
DOI: 10.1086/383309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macrolide Consumption on Erythromycin Resistance in Streptococcus pyogenes in Finland in 1997-2001

Abstract: The aim of this study was to investigate the association between regional macrolide resistance in Streptococcus pyogenes and macrolide use in Finland. During 1997-2001, a total of 50,875 S. pyogenes isolates were tested for erythromycin susceptibility in clinical microbiology laboratories throughout Finland. The local erythromycin resistance levels were compared with the regional consumption data of all macrolides pooled and, separately, with the use of azithromycin. The regional resistance rates of 1 year wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(102 citation statements)
references
References 21 publications
4
96
1
Order By: Relevance
“…Another group reported an ERY resistance rate of 23%, which was based on data collected over a 5-yr period (1997)(1998)(1999)(2000)(2001)(2002)(2003) in Seoul and Masan [10]. Changes in the prescription pattern of antibiotics or macrolide consumption could theoretically have an impact on the resistance rates to ERY for GAS [18,19], but these parameters are difficult to estimate without the respective data. If we assume that the production of drugs is closely correlated with consumption, we could utilize the production data to estimate their consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Another group reported an ERY resistance rate of 23%, which was based on data collected over a 5-yr period (1997)(1998)(1999)(2000)(2001)(2002)(2003) in Seoul and Masan [10]. Changes in the prescription pattern of antibiotics or macrolide consumption could theoretically have an impact on the resistance rates to ERY for GAS [18,19], but these parameters are difficult to estimate without the respective data. If we assume that the production of drugs is closely correlated with consumption, we could utilize the production data to estimate their consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed in Santa Catarina (South Brazil) in 2002 showed that 74% of the pharmacies offered antibiotic without any prescription [15]. This is a cause for concern as an increased consumption of antibiotics, such as erythromycin and tetracycline, correlates with an increase of resistance among GAS [16,17]. Two main well-described molecular mechanisms are responsible for macrolide resistance in GAS.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing ERY resistance in GAS isolates was noted in the 1990s, and in some countries, this resistance peaked in the early 2000s (5,7,8). The fluctuation in GAS macrolide resistance has been associated with changes in macrolide use (5,(8)(9)(10)(11).…”
mentioning
confidence: 99%